Comparison of Disability Rates After Traffic Accidents According to Legislation Regulations - Vural, Talip; Şener, Mustafa Talip; Kök, Ahmet Nezih (The Bulletin of Legal Medicine, 2022)
Objective: In this study; It was aimed to determine the differences of the estimated disability proportions between  the cases sent by the forensic units, and which applied individually to the Forensic Medicine Department with the aim of issuing a disability report due to traffic accidents, and to present suggestions in terms of which regulation is more useful.Material And Methods: A randomly selected sample size of  144 cases with a confidence rate of 95% and an expected 10% prevalence calculated with Epi-Info Version 7 program were retrospectively selected. The disability reports for this cases was given at Atatürk University Faculty of Medicine, Department of Forensic Medicine, to traffic accident happened  before 31.12.2018 according to the legal regulations.Results: 74.3% (n=107) of the cases were male and the mean age was 38.4 years. The average disability rate was found in the Regulation of Permanent Disabilities with 21.3%. The appreciation/comparison method was found most frequently in the Regulation of Permanent Disabilities as 29.9% (n=43).Conclusion: Due to its advantages such as the possibility of  inclusion in calculation of personal factors such as age and occupation, which are important in the compensation in the Regulation of Permanent Disabilities, and being suitable for the medical comparison/appraisal method, allowing the interpretation of the medical specialist who prepared the report, and results more significant for victims regulation in disability calculations, we think that the regulation of Permanent Disabilities is the most convenient.
Keywords: Forensic Medicine; Traffic Accident; Permanent Disability; Regulations Comparison